News and markets: The 2008 crisis from a neurofinance perspective—the case of BMFbovespa - Roberto Ivo da Rocha Lima Filho; Armando Freitas Rocha (Cogent Business & Management, 2017)
The world is still facing a financial crisis, which started in mid 2007 and up to now is far from being solved. Stock markets around the world reacted badly and the real-time news has never played such an important role to investors as seen in previous crisis. We used this model to study the Bovespa index (IBOV) evolution from January 2003 to September 2010 and correlated the market sentiment to an index of Good/Bad news about IBOV. Indeed news is found to have a major impact on market sentiment (volatility) and it is correlated with investors' humor. In other words, the impact of the media deepened the bearish dynamics of the markets.
Keywords: 650